Analysis of the Interpretation of the Meaning of the Karampuang Traditional House in Sinjai Regency - Kasdiawati Kasdiawati; Jeanny Maria Fatimah; Muhammad Farid (Research Synergy Foundation, 2021)
Karampuang traditional house is one of the cultural heritages that has symbols and meanings believed from generation to generation. This study aims to determine what symbols are contained in the Karampuang traditional house, both verbal and non-verbal, and to analyze the symbols. This research used qualitative method which the data were collected by using some techniques including: observation, in-depth interviews, documentation study, literature study, and field notes. The study used two data sources, primary data and secondary data. The technique of determining informants in this study was the purposive sampling technique. There were six informants. A traditional house consists of two houses. There are two renowned traditional houses, to wit; Arung and Gella. Arung’s house faces West, while Gella's traditional house faces East. The Roof of the house has two layers with a timpa laja’ in three layers. The roof Gella's is not double-decked and two-tiered; while the Arung’s composed of three of the timpa laja. In regard to the Islamic symbols in traditional houses, the houses are constructed with 30 house poles, as a symbol of the number of juz in the Quran. The 5 poles running north to south symbolize the 5 pillars of Islam; while 6 poles from west to east are a symbol of the six articles of faith. The ladder of the Karampuang traditional house only has one ladder with odd steps which the position is different from the house in general.The door of the house is located in Elle 'ri olo which is parallel right againts Salima'. Above the door, there is a stone that functions as a counterweight so that the door can be partially or completely open. The floor of a house made of bamboo is also called salima as a symbol of the rib which stretches from north to south called tunebbe'. The kitchen is located at the front that can be clearly seen when climbing the house’s ladder; in front of the door is a kitchen with two stoves located.